PENGARUH METODE SURVEY-QUESTION-READ-RECITED-REVIEW (SQ3R) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA SUB MATERI SISTEM EKSKRESI MANUSIA - Dede Julia; Sri Hartati (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2015)
The purpose of this study is to describe the feasibility SQ3R method on the materialsub human excretory system, analyzing the critical thinking skills of students in the submaterial human excretory system using SQ3R method, analyzing the critical thinking skills ofstudents in the sub-material human excretory system with conventional learning, analyzingthe effect of the method SQ3R to the critical thinking skills of students in the sub-materialhuman excretory system and describes the students' response to the use of SQ3R method insub-material human excretory system. This study departs from the idea that learning thematerial sub human excretory system using the method SQ3R can help students to betterconcentrate on the text they have read and make students use thinking skills in understandingthe main ideas / concepts in the text. Such learning can train students to develop criticalthinking skills. The research method used is the method of quasi-experimental researchdesign with non-equivalent control group design. Samples were taken as much as two classeswith saturated sampling techniques. The instrument used is the observation sheet,questionnaire, pretest and posttest form of description as much as 10 questions that havepreviously been tested. The results obtained the critical thinking skills of students in theexperimental class 70.32 and N-gain of 0.28 with the qualification being. Meanwhile, criticalthinking skills of students in the control classes 64,35 and N-gain of 0.28 with lowqualifications. Results of Mann-Whitney test on the N-gain obtained Z hitung 6.71 > 1.65 Ztabel thus Ho is rejected and Ha accepted. It is proved that there are significant SQ3Rstrategy on students' critical thinking skills in the sub-material human excretory system. Thisis supported by the average percentage of adherence to activity by 90% of teachers withexcellent qualifications, and the percentage of student responses by 71% with strongqualifications.